ÐÐ½Ð°Ð»Ð¸Ð· Ð±ÐµÐ»ÐºÐ¾Ð² Ð²Ð¸Ñ€ÑƒÑÑÐ¾Ð´ÐµÑ€Ð¶Ð°Ñ‰Ð¸Ñ… ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸Ð¹, Ñ…Ñ€Ð°Ð½Ð¸Ð²ÑˆÐ¸Ñ…ÑÑ Ð² ÑƒÑÐ»Ð¾Ð²Ð¸ÑÑ… ÑƒÐ¼ÐµÑ€ÐµÐ½Ð½Ð¾ Ð½Ð¸Ð·ÐºÐ¸Ñ… Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€ - Stegniy, M. Yu.; Semenchenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The authors have performed the analysis of proteins of non-purified suspensions of cattle diarrhea virus (DV), â€œOregon C-24 Vâ€ strain, subjected to freezing with a further storage at -18, -30Â°Ð¡ from 20 days to 10 years. At the same time there were revealed both the decrease of infectious activity and the degradation of virus-containing suspensions proteins, stored for a long time at moderately low temperature.